Oxidation of methyl linoleate with chemically generated singlet oxygen by the sodium molibdate/hydrogen peroxide system - Carlos Enrique Díaz; Freddy León; Martha Cecilia Daza; Fernando Martínez (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
Oxidation of the methyl linoleate with singlet oxygen, generated chemically by the sodium molybdate/hydrogen peroxide system (Na2 MoO4 /H2 O2 ), was studied in a type microemulsion micelle inverted (O/W). The monitoring of methyl linoleate oxidation with singlet oxygen was carried out using a UVVis spectrocopy, measuring the absorbance at 234 nm corresponding to the conjugated hydroperoxides. Under room temperature and pressure, products of the decomposition of possible dioxetane were not identified by HPLC and GC-MS, as some studies have suggested.